Cutaneous manifestations of obesity in children: A prospective study - Mrinal Gupta (Wolters Kluwer Medknow Publications, 2017)
Background: Obesity is a chronic disorder with rising prevalence that affects several organs, including the skin. Although it is more common in adults, the prevalence in the pediatric population is growing rapidly. Obesity is associated with a large number of cutaneous manifestations which are directly related to the age of onset and duration of obesity. Materials and Methods: This was a prospective study in which children aged 3 years or more with body mass index (BMI) >30 kg/m2 were included in the study. After informed consent from the parents/attendants, demographic details, height, and weight were documented. All the children were subjected to a detailed dermatological examination by an experienced dermatologist, and all the cutaneous changes were carefully recorded in a predesigned pro forma. Results: A total of 100 children (male: 61, female: 39) were included in the study. The mean age of the participants was 11.3 ± 1.3 years and the mean BMI was 32.6 ± 1.36 kg/m2. Majority of the patients (71%) had Class I obesity (BMI 30.00-34.99) while 27% had Class II obesity (BMI 35.00-39.99). The most common cutaneous manifestations among the children were acanthosis nigricans (42%), striae (19%), fungal infections and intertrigo (16%), acrochordons (12%), acne (10%), hirsutism (8%), and viral and bacterial infections (5%). Other less common associations were psoriasis, xanthomas, corns, plantar hyperkeratosis, and miliaria. Conclusion: Likewise in adults, obesity is associated significantly with certain dermatoses in children also. As the prevalence of obesity is increasing each day, understanding of these dermatoses is necessary both for the pediatricians as well as for dermatologists for early diagnosis and management.